2021
DOI: 10.13057/biodiv/d220359
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-glucosidase activity, metals content, and phytochemical profiling of Andrographis paniculata from different geographical origins based on FTIR and UHPLC-Q-Orbitrap HRMS metabolomics

Abstract: Abstract. Rafi M, Septaningsih DA, Karomah AH, Lukman, Prajogo B, Amran MB, Rohman A. 2021. Inhibition of α-glucosidase activity, metals content, and phytochemical profiling of Andrographis paniculata from different geographical origins based on FTIR and UHPLC-Q-Orbitrap HRMS metabolomics. Biodiversitas 22: 1535-1542. Ensuring consistency of quality, safety, and efficacy of herbal medicines from raw materials to finished products is important because of the variability in medicinal plants' active components. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…As the biomarker of this plant, andrographolide was tested, and the IC 50 was 11.0 ± 0.28 mg/ mL. 29 On the other study 30 showed IC 50 of Andrographis paniculata and andrographolide better than Subramanian et al According to those studies, it proves that andrographolide has antidiabetic activity as an alpha-glucosidase inhibitor. The IC 50 of Syzygium cumini extract and Caesalpinia sappan extract did not make much difference, while the IC 50 of Andrographis paniculata extract obtained better results than previous studies.…”
Section: Alpha-glucosidase Inhibitory Activity Assaymentioning
confidence: 95%
“…As the biomarker of this plant, andrographolide was tested, and the IC 50 was 11.0 ± 0.28 mg/ mL. 29 On the other study 30 showed IC 50 of Andrographis paniculata and andrographolide better than Subramanian et al According to those studies, it proves that andrographolide has antidiabetic activity as an alpha-glucosidase inhibitor. The IC 50 of Syzygium cumini extract and Caesalpinia sappan extract did not make much difference, while the IC 50 of Andrographis paniculata extract obtained better results than previous studies.…”
Section: Alpha-glucosidase Inhibitory Activity Assaymentioning
confidence: 95%
“…The peak at 2927 cm -1 was due to the asymmetric stretching of the C-H and C=H bonds (Ahmed et al 2017;Nair and Mukne 2017). The peak at 1662 cm -1 was associated with the tertiary amides C=O stretching (Roy et al 2015;Rafi et al 2021). The peaks at 1598 and 1513 cm -1 were assigned to stretching C=N and C=C bonds in the α-helix and β-sheet structures of proteins (amide I and amide II, respectively) (Ahmed et al 2017).…”
Section: Ftirmentioning
confidence: 99%
“…18 Through an untargeted metabolomics approach, known and previously unknown compounds with novel structures and bioactivities may be identified under specific conditions. [19][20][21] Metabolomics analysis can further reveal relationships among active metabolites and bioactivities. [22][23][24][25] However, there have been no comprehensive metabolomics analyses of compounds active on ER-positive breast cancer in soursop leaf extract.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics allows for identifying and quantifying metabolites produced by a biosystem at a particular time 18 . Through an untargeted metabolomics approach, known and previously unknown compounds with novel structures and bioactivities may be identified under specific conditions 19–21 . Metabolomics analysis can further reveal relationships among active metabolites and bioactivities 22–25 .…”
Section: Introductionmentioning
confidence: 99%